2018
DOI: 10.1186/s13047-018-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and correlates of cross‐sectional area of abductor hallucis and the medial belly of the flexor hallucis brevis measured by ultrasound

Abstract: BackgroundWeakness of the intrinsic foot muscles is thought to produce deformity, disability and pain. Assessing intrinsic foot muscles in isolation is a challenge; however ultrasound might provide a solution. The aims of this study were to assess the reproducibility of assessing the size of abductor halluces (AbH) and the medial belly of flexor hallucis brevis (FHBM) muscles, and identify their relationship with toe strength, foot morphology and balance.MethodsTwenty one participants aged 26–64 years were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 95 publications
(132 reference statements)
1
32
2
Order By: Relevance
“…Fear of falling score clinically improved following 4 weeks of TENS compared with the CON group, possibly due to an increase in the strength of intrinsic foot muscles in the elderly, similar to the findings of a previous study [38]. The study of Hashimoto and Sakuraba (2014) [39] confirmed that strengthening the AbdH muscle results in better standing and walking performance.…”
Section: Discussionsupporting
confidence: 86%
“…Fear of falling score clinically improved following 4 weeks of TENS compared with the CON group, possibly due to an increase in the strength of intrinsic foot muscles in the elderly, similar to the findings of a previous study [38]. The study of Hashimoto and Sakuraba (2014) [39] confirmed that strengthening the AbdH muscle results in better standing and walking performance.…”
Section: Discussionsupporting
confidence: 86%
“…There were a few limitations in this study related to the ultrasound imaging methods. First, due to the FHL tendon location and double muscle head of the FHB, current methodology to obtain a CSA for FHB is dependent on the ultrasound operator to subjectively locate the thickest part of the muscle [19,50]. We chose a simpler thickness measurement at a uniform distance from the sesamoid bone of the hallux.…”
Section: Limitations and Futurementioning
confidence: 99%
“…Although optimal US settings (eg, transducer and frequency selection, depth, and focus position) are assumed across studies, transducer placement strategies and techniques have not been well standardized. Measurements of the foot muscles, for example, have been performed at the thickest part of the muscle, 50% of the foot length, and various positions on the leg referenced to internal bony landmarks . When measuring the abductor hallucis (ABDH) thickness, Mickle et al 20 found higher intraclass correlation coefficients (ICCs) and lower limits of agreement (LoAs) when using the medial malleolus landmark as opposed to the thickest part of the muscle, suggesting that the use of landmarks is likely more reliable than image‐based subjective locations.…”
mentioning
confidence: 99%